Highlight Test Code: Visualizing the Co-Evolution of Test and Production Code in Software Repositories - Miranda, Charles; Avelino, Guilherme; Santos Neto, Pedro (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2025)
The asynchronous evolution of test and production code can compromise software quality and maintainability. However, identifying and analyzing such co-evolution dynamics remains a complex task, often hindered by the lack of scalable tools and comprehensive visualizations. This paper presents Highlight Test Code, a web-based platform for analyzing the co-evolution of test and production code in open-source repositories. The platform implements a multi-stage pipeline encompassing repository mining, time series generation, clustering, and statistical correlation. It is built upon a curated dataset of 526 GitHub repositories across six programming languages. Highlight Test Code offers visual analytics and AI-generated insights that assist users in identifying test evolution patterns, evaluating co-evolution levels, and understanding their relationship with maintenance activities and project characteristics. The tool enables researchers and practitioners to assess testing practices at scale. Video link: https://youtu.be/U29eEg_gXXM . Software License: General Public License (GPL).